Guiding antiferromagnetic transitions in Ca $$_{2}$$ 2 RuO $$_{4}$$ 4 - D. G. Porter; F. Forte; V. Granata; M. Cannavacciuolo; R. Fittipaldi; M. Cuoco; A. Bombardi; A. Vecchione (Scientific Reports, 2022)
Abstract Understanding and controlling the transition between antiferromagnetic states having different symmetry content with respect to time-inversion and space-group operations are fundamental challenges for the design of magnetic phases with topologically nontrivial character. Here, we consider a paradigmatic antiferromagnetic oxide insulator, Ca $$_{2}$$ 2 RuO $$_{4}$$ 4 , with symmetrically distinct magnetic ground states and unveil a novel path to guide the transition between them. The magnetic changeover results from structural and orbital reconstruction at the transition metal site that in turn arise as a consequence of substitutional doping. By means of resonant X-ray diffraction we track the evolution of the structural, magnetic, and orbital degrees of freedom for Mn doped Ca $$_{2}$$ 2 RuO $$_{4}$$ 4 to demonstrate the mechanisms which drive the antiferromagnetic transition. While our analysis focuses on a specific case of substitution, we show that any perturbation that can impact in a similar way on the crystal structure, by reconstructing the induced spin–orbital exchange, is able to drive the antiferromagnetic reorganization.